Pelatihan Kerajinan Pot dari Semen dan Handuk Bekas Guna Menumbuhkan Kreativitas Masyarakat - M Farid Nasrulloh; Khusnul Khotimah; Wiwid Ika Hariyanti; Siti Rochmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
Residents who live in this area on average plant certain types of flowers in flower pots, they buy flower pots at a fairly high price. Flowers with aglonema type need a pot as a place to grow. This community service activity is carried out to foster knowledge and understanding of PKK mothers and IPNU and IPPNU youth in utilizing unused objects that can be processed into products that have added value and are very useful which is termed Upcycle. The pot training activity from used cloth is carried out to train the community to use used cloth which can be a product that has high artistic value. This community service activity uses a training method for making pots from cement and used towels. The results of this activity are (1) It can foster the creativity of PKK mothers and IPNU IPPNU teenagers in utilizing used goods such as used towels. (2) PKK mothers and IPNU IPPNU youth have new knowledge about the utilization of unused used goods in the surrounding environment to be processed into useful products and have a high buying and selling value. (3) PKK mothers and IPNU IPPNU youths can save money on buying similar products that can be made by themselves.